The new association in xeromesophilic oak forests of Aceri tatarici–Quercion roboris alliance (class Quercetea pubescentis) in the basin the lower Sula (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
Association Violo hirtae–Quercetum roboris is discribed as new for science from the basin of the lower Sula. Its xeromesophilic oak forests which are represented by three subassociations. They are attributed to the Aceri tatarici-Quercion roboris alliance. They are rare and occupy the driest ecotops of the plankers (the fourth floodplain terraces) above the ditches, between the ridges of beams, at the top of the slopes. They perform important anti-erosion and soil protection functions.
Keywords: Violo hirtae–Quercetum roboris river valley, Ukraine.